The strategies in requests and apologies of Turkish FLED students: a comparison of electronic mails and DCT data - Eliçin, Canan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The aim of this study is to analyze and compare the e-mail messages and Discourse Completion Test (DCT) data of the students at Foreign Language Education Department (FLED) at an English medium university in order to investigate the strategies and categories they use when performing requests and apologies. The study further investigates English L1 speakers’ (EL1) and Turkish L1 speakers’ (TL1) responses to the DCT to make a cross-cultural comparison between the FLED students and the ESP group and to detect cross-linguistic influences from the first language (L1). The data were collected through e-mails from FLED students, and DCTs from the three groups of the participants. The data were coded and categorized so as to display the frequency and the percentages of the strategies for each group. The results of statistical analyses suggest a significant difference between e-mail and DCT data regarding the frequency of the use of request and apology strategies by FLED students. Findings indicate both similarities and differences between the ESP group and FLED students. The ESP group used certain request strategies at a significantly higher/ lower rate than the FLED students. Finally, Turkish FLED students borrowed from their L1 pragmatic knowledge when performing certain request and apologizing strategies.
Keywords: Language and languages -- Study and teaching.; Apologies.